Unsuccessful Treatment of Cheilitis Granulomatosa with Oral Methotrexate - Thanapon Sutharaphan (2020)
© 2019 The Author(s). Published by S. Karger AG, Basel. Cheilitis granulomatosa (CG) is a rare idiopathic condition with painless lip swelling, characterized by non-necrotizing granulomatous iniammation in the absence of other identifiable causes such as Crohn's disease, sarcoidosis, foreign body reaction, or infection. CG may precede the presentation of Crohn's disease after long-term follow-up. Spontaneous remission of CG rarely occurs. To date, given the rarity of CG, there is no gold standard treatment. Recommended treatments are supported by small studies, case reports/series, and expert opinions. Glucocorticoids are the first-line therapy in the acute stages of the disease; however, recurrence commonly occurs. Previously, methotrexate (MTX) showed a beneficial effect on orofacial swelling in a case of CG accompanied by Crohn's disease. We present a patient with CG without Crohn's disease. He was treated with oral MTX in combination with intralesional corticosteroid injection on one side of the lip. The injected side showed improvement, while lip swelling on the noninjected area remained unchanged after 3 months of treatment. Therefore, CG is refractory to treatment with MTX from our experience. Further studies regarding the optimum dosage of MTX is needed.